PENYUSUNAN LAPORAN KEUANGAN BERBASIS SAK ETAP (Studi Kasus pada Perusahaan Tempe Keripik Bintang Selera Ngawi) - Ali Nur Rohman Suharno (Universitas Slamet Riyadi, 2014)
The system is essential in business activity, especially businesses that have complex transactions. Regardless of the increasing complexity of business activities and transactions are also diverse, it is necessary to the management of operational activities that can be controlled properly. The results of the accounting system is a form of information that can be used to determine the company's financial condition and automatically establish the internal control system (SPI) which serves as a control to monitor the course of a system that has been running the company as well as to ensure that the operational activities are effective. This study uses a case study conducted on the owners and employees of companies tempe chips